2017
DOI: 10.1016/j.ijscr.2017.07.050
|View full text |Cite
|
Sign up to set email alerts
|

Case report of successful partial splenectomy for a splenic abscess in a paediatric patient

Abstract: HighlightsSplenic abscess is rare conditions seen in children.Salmonellosis is a common cause of infection in splenic abscess.Splenic abscess can be managed with partial splenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Isolated splenic abscesses are a dangerous, but fortunately uncommon condition in children requiring a high degree of clinical suspicion. 1 3 The triad of fever, upper quadrant abdominal pain, and leukocytosis is not specific but should raise suspicion for a splenic abscess. 2 , 3 , 6 In addition to these signs and symptoms, patients may complain of left shoulder pain due to involvement of diaphragmatic pleura, and shortness of breath in the presence of splenomegaly and pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Isolated splenic abscesses are a dangerous, but fortunately uncommon condition in children requiring a high degree of clinical suspicion. 1 3 The triad of fever, upper quadrant abdominal pain, and leukocytosis is not specific but should raise suspicion for a splenic abscess. 2 , 3 , 6 In addition to these signs and symptoms, patients may complain of left shoulder pain due to involvement of diaphragmatic pleura, and shortness of breath in the presence of splenomegaly and pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…A clinical presentation of fever, upper abdominal pain, and leukocytosis should raise the possibility of splenic abscess; risk factors include infections at a distant or contiguous site, splenic trauma, hemoglobinopathies, and an underlying state of immunocompromise. 1 Due to the wide variety of causative pathogens, broad empiric antimicrobial coverage and comprehensive evaluation for the source of infection are required. Historically, the treatment strategy for splenic abscesses included splenectomy and antimicrobial therapy; however, accumulated evidence has demonstrated that percutaneous aspiration with antimicrobial therapy has a high success rate.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a clear tendency to increase the percentage of non-radical splenic interventions over total splenectomy. This results from greater awareness of the important role of spleen in the removal of encapsulated bacteria (12,14) . Percutaneous drainage is more preferable than surgical drainage due to the lack of postoperative complications, shorter hospital stay and lower treatment costs (13) .…”
Section: Discussionmentioning
confidence: 99%